Knowledge of Pedagogical Competence Toward Teachers with and Without Educational Background - Hidayatullah, Heri; Qomariyah, Siti Syafi’atul; Krisnahadi, Tama; Mukminah, Mukminah (LPPM Universitas Nahdlatul Ulama Nusa Tenggara Barat, 2025)
The recruitment of teachers should consider at least two criteria by any institution before proceeding the next step of the recruitment. The two criteria are the teachers’ academic qualification and the teachers’ competency. This research aimed to find out whether the teacher with educational and without educational background have significant effect on the knowledge of pedagogical competence or not. Quasi-experimental research with pretest posttest nonequivalent comparison group design was applied in this research by which all teachers affiliated in PERGUNU Lombok Tengah as the population. The purposive sampling technique is used to determine the samples (two experimental group). The instrument which was in the form of pedagogical test had been tested its validity and reliability was distributed to collect the data needed and then the data was analyzed using ANOVA. The result showed that the score of F-test was higher than F-table in the significant level of 0.5. It meant that the teachers with educational background have a basic knowledge of pedagogical competence. However, the teachers without educational background had no basic knowledge of such competence. It could be concluded that there was a significant effect of teachers with educational background toward the knowledge of pedagogical competence comparing to those teachers without any educational background. In other words, the null hypothesis of this research was accepted and the alternative hypothesis was rejected.